Sprint versus isolated eccentric training: Comparative effects on hamstring architecture and performance in soccer players - Mendiguchia, J.; Conceição, F.; Edouard, P.; Fonseca, M.; Pereira, R.; Lopes, H.; Morin, J.-B.; Jiménez-Reyes, P. (PLOS ONE, 2020)
Aims: The purpose of this study was to compare the effects of hamstring eccentric (NHE) strength training versus sprint training programmed as complements to regular soccer practice, on sprint performance and its mechanical underpinnings, as well as biceps femoris long head (BFlh) architecture. Methods: In this prospective interventional control study, sprint performance, sprint mechanics and BFlh architecture variables were compared before versus after six weeks of training during the first six preseason weeks, and between three different random match-pair groups of soccer players: "Soccer group" (n = 10), "Nordic group" (n = 12) and "Sprint group" (n = 10). Results: For sprint performance and mechanics, small to large pre-post improvements were reported in "Sprint group" (except maximal running velocity), whereas only trivial to small negative changes were reported in "Soccer group" and "Nordic group". For BFlh architecture variables, "Sprint" group showed moderate increase in fascicle length compared to smaller augment for the "Nordic" group with trivial changes for "Soccer group". Only "Nordic" group presented small increases at pennation angle. Conclusions: The results suggest that sprint training was superior to NHE in order to increase BFlh fascicle length although only the sprint training was able to both provide a preventive stimulus (increase fascicle length) and at the same time improve both sprint performance and mechanics. Further studies with advanced imaging techniques are needed to confirm the validity of the findings.